(untitled) (LACCEI, 2024)
Abstract - The present study had the objective of determining the influence of a TMS system for efficiency in the supply chain of San Fernando in Lima-Peru 2022. The approach was quantitative of the applied type, with a pre-experimental design. The population for this study consisted of 44 employees directly related to the activities of the supply chain of San Fernando S.A. with a census sample which consolidates the entire population. The data collection technique for this study is the survey and the observation sheet. Primary data, obtained by questionnaires that were validated by the expert judgment method, with a reliability level of 88%, were analyzed. As well as secondary data of indicators of the enterprise resource planning (ERP) system (before the implementation of the TMS) and the TMS database (after the implementation). In addition, the SCRUM framework was used. In this sense, the development and successful implementation of the TMS demonstrated a positive impact on the efficiency of supply chain operations, with a specific impact of 21.60% improvement in efficiency in delivery time management, 23.20% of improvement in total transportation costs and a 29.20% improvement in data quality.